Fabrication of oil-in-water emulsions as shelf-stable liquid non-dairy creamers: effects of homogenization pressure, oil type, and emulsifier concentration - Soo, Yuen Num; Tan, Chin Ping; Tan, Phui Yee; Khalid, Nauman; Tan, Tai Boon (Wiley, 2020)
The popularity of coffee, the second most consumed beverage in the world, contributes to the high demand for liquid non‐dairy creamer (LNDC). In this study, palm olein emulsions (as LNDCs) were investigated as alternatives to the more common soybean oil‐based LNDCs. LNDCs were prepared via different homogenization pressures (100–300 bar) using different types of oil (palm olein and soybean oil) and concentrations of DATEM emulsifier (5–20 g kg−1).Increases in homogenization pressure and emulsifier concentration were observed to have significant ( P < 0.05) effects on the physicochemical properties (particle size, pH, and viscosity) of the LNDCs. Palm olein and soybean oil LNDCs prepared using 15 g kg−1 and 10 g kg−1 DATEM emulsifier, respectively, were determined to be the most stable (as observed throughout a 15‐day storage period at ambient temperature of 28 ± 2 °C), with properties closest to those of a commercial LNDC. When added to black coffee, both LNDCs displayed a good whitening effect by increasing the L* value from 26.73 ± 0.16 (black coffee) to ≥40.82 ± 0.56 (black coffee + LNDCs). Sensory evaluation showed that there were no significant ( P > 0.05) differences between the prepared and commercial LNDCs in terms of their color, appearance, and overall acceptability.Shelf‐stable LNDCs with qualities comparable to commercial LNDC were successfully fabricated. Valuable insights into the effects of homogenization pressure, oil type, and emulsifier concentration, as well as functionality and consumer acceptance of the LNDCs when added into black coffee, were obtained.